Consent to Donate Surgical Biospecimens for Research: Perceptions of People With Colorectal Cancer. Issue 3 (May 2016) - Williams, Anne Marjorie; Allen, Judy; Zeps, Nikolajs; Pienaar, Catherine; Bulsara, Caroline; Monterosso, Leanne
Abstract : Background: Biospecimens for cancer research are commonly sought from people who undergo surgery for a new diagnosis of cancer, and the demand for these biospecimens is increasing. Objective: The objective of this study was to explore the perceptions of people with colorectal cancer regarding the impact of an opt-in model of consent for biospecimen donation. Methods: The qualitative method of Grounded Theory was used, and data were gathered through digitally recorded semistructured interviews with 18 participants. Data were analyzed using the constant comparative method to the descriptive level. Results: Four major categories were identified describing the response to the consent process used for donating tissue for research purposes. These were as follows: consent is "no big deal" compared with the diagnosis of cancer; helping others; trusting the surgeon; and information related to donation of biospecimens. Conclusions: Results from this study indicate that the achievement of ideal informed and voluntary consent is difficult when patients are confronted with the trauma of newly diagnosed illness. Innovative approaches are implicated to obtain consent while protecting the autonomy and dignity of patients. Implications for Practice: The results from this study can contribute to further development of processes for the donation of biospecimens for research purposes that respect the needs and views of patients.